Overdose and intramuscular administration of Bacille Calmette-Guerin vaccine in a 2-month-old infant - (:unkn) unknown (TURKISH J PEDIATRICS, 2014)
The Bacille Calmette-Guerin (BCG) vaccine is used against tuberculosis. According to the vaccination program in Turkey, DaBT-Hib-IPV (diphtheria-pertussis [acellular]-tetanus-haemophilus influenza type b-inactive polio vaccine), PVC13 (pneumoccocal conjugate vaccine) and BCG vaccines are given simultaneously to all 2-months-old infants, using different administration techniques. We report a 2-month-old infant who received an overdose and intramuscular BCG vaccine instead of DaBT-Hib-IPV. The patient was treated with isoniazid for six months and developed no complications during a one-year follow-up period.
Keywords: infant; overdose and intramuscular BCG vaccine; BCG VACCINE